A golden ratio as a generalization of the 2/3 rule of Janusz Łyko - Maciuk, Arkadiusz; Smoluk, Antoni (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
A golden ratio has been applied since ancient times in many areas, starting with architecture and art, and nowadays in modern financial markets and contemporary physics. This paper defines a golden rule in a set of preferences, generalizing the problem of group choice and the 2/3 rule of Łyko by means of a golden number corresponding to the ratio of lengths of sides in a golden rectangle
Mathematical Economics, 2018, Nr 14 (21), s. 31-36
Keywords: golden number; problem of group choice; 2/3 rule